PENERAPAN MARKETING KOMUNIKASI DALAM MENANGANI KOMPLAIN ONLINE TAMU DI VANILLA HOTEL BATAM - Erwina; Okki Kurnia (JURNAL MEKAR, 2022)
The purpose of communication is to inform, persuade and remind. However, some of the communications delivered are not aligned with the intended purpose, thus triggering a complaint. The formulation of the problem in this study is to find out how marketing communication and online complaints are with the research location at Vanilla Hotel Batam. This research-based is on the theory of marketing communication by Hermawan with 5 indicators (promotion, advertising, personal selling, public relations, direct marketing) and on theory of complaint by Tjiptono with 3 indicators (speed of complaint handling, problem solving, ease of complaint filing procedure). The research was conducted using qualitative research methods. Data collection techniques were carried out through observation, literature study, and interviews with hotel manager, senior sales and marketing, and reservation agents. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results of the analysis show that the application of communication marketing at Vanilla Hotel Batam is quite good in indicators (promotion, advertising, personal selling, public relations, direct marketing). However, the complaint indicator needs to be improved. Based on the results of the analysis, it is expected that Vanilla Hotel Batam can increase its human resources and consider conducting training for the front office and sales and marketing departments.